Use of Complex DNA and Antibody Microarrays as Tools in Functional Analyses. Issue 5 (2003) - Bauer, Andrea; Beckmann, Boris; Busold, Christian; Brandt, Ole; Kusnezow, Wlad; Pullat, Janne; Aign, Verena; Fellenberg, Kurt; Fleischer, Robert; Jacob, Anette; Frohme, Marcus; Hoheisel, Jörg D.
Abstract : While the deciphering of basic sequence information on a genomic scale is yielding complete genomic sequences in ever-shorter intervals, experimental procedures for elucidating the cellular effects and consequences of the DNA-encoded information become critical for further analyses. In recent years, DNA microarray technology has emerged as a prime candidate for the performance of many such functional assays. Technically, array technology has come a long way since its conception some 15 years ago, initially designed as a means for large-scale mapping and sequencing. The basic arrangement, however, could be adapted readily to serve eventually as an analytical tool in a large variety of applications. On their own or in combination with other methods, microarrays open up many new avenues of functional analysis.